I. Sáez-Rosenkranz y J.Prats Cuevas (eds.). (2020). Memoria histórica y enseñanza de la Historia. Gijón: Ediciones Trea. 212 pp., ISBN: 978-84-18105-38-8 - Ortega Cervigón, José Ignacio (Panta Rei. Revista digital de Historia y Didáctica de la Historia, 2022)